Granting of Lithuanian Citizenship in Biržai District During the Interwar Period - Birgiel, Paulius (Acta humanitarica academiae Saulensis, 2025)
The article examines Lithuanian state institutions’ effect on Biržai district inhabitants’ citizenship and permanent residence aspirations during the interwar period. By utilizing Lithuanian Central State Archive documents and other complementary historical sources, the paper aims to survey regional administration ethnic differentiation practices, outline stateless groups’ citizenship struggles, and present ambiguous individual attitudes towards nationality. The study suggests that the state elite’s homogeneous society vision was difficult to adjust to people’s interests. The lack of citizenship self-awareness among the Lithuanian population caused pragmatical citizenship assessments, which was also present for many Biržai district inhabitants who aspired to become owners of the agricultural land. Since Lithuanian state institutions were convinced that the majority of the population was unable to self-identify by nationality, they enforced more control in the process of granting citizenship.
Keywords: Lithuanian citizenship; Biržai district; ethnic differentiation; county self-government